Human resources security as an element of economic security in region - N. V. Borovskikh; E. A. Kipervar (Омский научный вестник: Серия "Общество. История. Современность")
The article presents an analysis of the essence of the personnel security of the region as an element of economic security of the subject of the Russian Federation. The types of personnel security threats are described and characterized, the comparative characteristic of the level of personnel security of various socio-economic systems, including the country, region and enterprise, is given. The indicators describing the demographic and socio-economic threats to human resources in the Omsk region are proposed and analyzed. The basic tendencies of demographic and social and economic development of the region are singled out, actions on decrease of threats of personnel safety are offered